PERAN KOMISI PENGAWAS PERSAINGAN USAHA SEBAGAI WASIT SEKALIGUS HAKIM DALAM EKONOMI - Dewi, Ratna; Timori, Helmin Porang; S, Moh. K. Aripin; Zakariya, Ali; Putri, Audrey Aulia; Taena, Markus; Ramadhanty, Andiera Eko (Collegium Studiosum Journal, 2024)
The Business Competition Supervisory Commission (KPPU) is a state institution that has a crucial role in maintaining balance and fairness in the dynamics of the Indonesian market. As a supervisor of business competition, KPPU functions as a referee who ensures that all business actors play by the same rules. Its main task is to prevent monopolistic practices, cartels, and other unfair competition that can harm consumers and hinder economic growth. The purpose of this study is to determine the problems faced by KPPU in carrying out its duties. The research method used is normative juridical. The data analysis is by using the Qualitative method. The results of the study are that in carrying out its duties, KPPU still faces a number of challenges. One of the main challenges is the increasing complexity of business competition cases, especially along with the development of technology and globalization. In addition, KPPU also needs to continue to improve the capacity of its human resources in order to handle cases more quickly and effectively. The conclusion is that KPPU needs to continue to make various efforts, such as strengthening coordination with related institutions, increasing public awareness of the importance of healthy business competition, and developing information technology to support the supervision process. KPPU also needs to continue to conduct studies and research to understand the latest developments in market dynamics and business competition. In the increasingly developing digital era, KPPU also needs to pay attention to the development of digital technology and its impact on business competition. For example, KPPU needs to anticipate the potential for monopolies or cartels in digital platforms, and ensure that digital innovation does not hinder healthy competition. By carrying out its dual role as referee and judge effectively, KPPU can contribute significantly to realizing a fair, efficient, and competitive Indonesian economy.